Analysis of scientific production and knowledge about wildlife roadkill in Brazilian protected areas - Miranda, Jefferson; Schiavetti, Alexandre (Ethnobiology and Conservation, 2024)
Roads are responsible for great biodiversity loss, especially in protected areas (PAs). Thus, considering the great risk of roads to PAs and the lack of knowledge about these areas, we aimed to analyze the scientific production on wildlife roadkill in Brazil and compare the studies that surveyed roads with and without PAs. We searched for papers in five databases: SciELO, Google Scholar, Reet Brasil, Scopus and Plataforma Lattes. Studies considered to be near PAs (PPA) collected data within a radius of 1km of PAs and the other studies were considered to have no PA (NPA). We found 126 studies that surveyed wildlife roadkill in Brazil, of which 57% are PPA. Publications on wildlife roadkill have increased in recent years, with a greater number of PPA studies than NPA studies (W = 618, p = 0.5992). Mammals are the most-studied group (n = 108), followed by reptiles (n = 79), birds (n = 73) and amphibians (n = 58). Most of the studies took place in the Cerrado (54) and the Atlantic Forest (45), where are the greatest number of surveyed PAs, greatest number of PAs and greatest number of PAs without studies. Only 18 papers suggest specific mitigation measures for the study site. The increase in PPA studies is positive, but researchers need to increase contact with PA managers to produce scientific knowledge and develop more efficient mitigation measures for these areas. We encourage increased surveying of roads near PAs, involvement of researchers with environmental agencies, and more studies with small animals.